Duration of breastfeeding and the risk of childhood asthma in children living in urban areas - Fonseca, Maria João (2010)
Asthma is one of the most common chronic diseases during childhood, and the role of breastfeeding in its developmentremains controversial. Our objective was to quantify the association between the duration of breastfeeding and the occurrence of asthma in infancy.